2006
DOI: 10.1556/avet.54.2006.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Toxocara infection in the environment and in definitive and paratenic hosts in Estonia

Abstract: The aim of the study was to elucidate the distribution and possible transmission routes of Toxocara spp. infection in Estonia. Out of 454 faecal and sand samples collected from park lawns and sandpits in the town of Tartu, 19 were Toxocara positive (4.2%). Out of the 45 sandpit samples 17.8% were Toxocara positive. Cat faeces was found in 21 sandpit samples. Parasitological necropsies were performed on 41 euthanised stray dogs and 27 cats in the Tallinn Dog Home. Additionally, 13 wild free-roaming brown rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Arbabi and Hooshyar in central Iran and Sadjjadi et al in southern Iran reported 13.3% and 52.8%, respectively [20], [30]. One study in Turkey showed that the prevalence of T. cati was 62.5% [31] whereas other studies in Estonia and Ireland reported a prevalence of 48.2% and 42.8% in adult cats, respectively [32], [33]. It seems that the higher prevalence of T. cati in our study is probably because of the climatic conditions, which are suitable for the spread and survival of helminth eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Arbabi and Hooshyar in central Iran and Sadjjadi et al in southern Iran reported 13.3% and 52.8%, respectively [20], [30]. One study in Turkey showed that the prevalence of T. cati was 62.5% [31] whereas other studies in Estonia and Ireland reported a prevalence of 48.2% and 42.8% in adult cats, respectively [32], [33]. It seems that the higher prevalence of T. cati in our study is probably because of the climatic conditions, which are suitable for the spread and survival of helminth eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Human infection can occur as a result of ingesting embryonated eggs from the environment such as contaminated vegetables and fruits (Dubinský et al 1995;Magnaval et al 2001;Talvik et al 2006), although the possibility of ingestion of larvae within small paratenic hosts, such as beetles, or in uncooked meat, cannot be excluded (Fisher 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The number of dogs and cats, especially in urban areas, is ever so increasing, so their share on environmental contamination with Toxocara eggs has often been discussed. But stray cats still play an important role in epidemiology of toxocariasis (Talvik et al, 2006). …”
Section: Introductionmentioning
confidence: 99%